Atributos químicos do solo e desempenho de culturas em rotação ou consórcio com plantas de cobertura em sistema agroflorestal - Arruda, Everton Martins (2017)
The presence of an arboreal component, such as in agroforestry systems, can promote a better balance of tropical ecological processes, allowing agricultural exploration in vertical and horizontal landscape profiles. This, together with the inclusion of single or intercropped cover crops in the agroforestry understory can increase the beneficial effects through interaction among species, favoring greater nutrient accumulation and cycling. Therefore, the objective of this research was to evaluate the soil chemical attributes and the performance of agricultural species and cover crops in rotation/consortium in an agroforestry system in the cerrado region of Goiás. The research was carried out between 2012 and 2016, in the city of Goiânia-Goiás, in an agroforestry system implanted in an 8- year-old Baru forest (Dipteryx alata V.). Soil from the experimental area was classified as typical dystrophic Red Latosol. The experimental design was randomized complete block (RCB), with four replications. Cover plants were cultivated singly: Pigeon pea (Cajanus cajan); Stylosanthes cv. Campo Grande (Stylosanthes macrocephala - 20% and Stylosanthes capitata - 80%); Massai grass (Panicum maximum) and intercropped: Pigeon pea+ Massai grass and Stylosanthes + Massai grass, in addition to an area under spontaneous vegetation (control treatment). We evaluated soil chemical fertility and dry phytomass productivity and macronutrient accumulations by cover crops, quality and yield of corn silage grown in rotation with the cover plants, relative index of chlorophylls and growth of Banana trees cultivated in consortium with the cover plants, in addition to the growth of the Baru trees during this period (height, diameter at breast height and crown diameter). The Campo Grande Stylosanthes increased the calcium contents, pH values and sum of bases in the soil solution at depth 0-10 cm after two years of cultivation. However, Massai grass, alone, increased potassium levels at depth 0-10 and 10-20 cm in the same cultivation year. The dry matter yield of silage maize was similar among the residual straw of Pigeon pea, Massai grass, and Stylosanthes + Massai grass cultivars. However, cultivation with residual Stylosanthes increased the crude protein percentage. The growth in height of the banana trees at 6 and 12 months was higher in consortium with Massai grass when compared to the area maintained with spontaneous vegetation. The incremental increase in height of Baru trees only increased after two years through the residual Campo Grande Stylosanthes. The highest productivity of dry phytomass was obtained from Massai grass, alone. The accumulations of nitrogen, phosphorus, calcium and sulfur were similar among Massai grass alone, Stylosanthes alone, and Massai grass + Stylosanthes consortium. However, potassium and magnesium accumulations were only higher in the aerial part of the Massai grass, alone.